Diffusion-weighted magnetic resonance imaging in the differentiation of endometriomas from hemorrhagic cysts in the ovary. (August 2016) - Lee, Nam Kyung; Kim, Suk; Kim, Ki Hyung; Suh, Dong Soo; Kim, Tae Un; Han, Ga Jin; Lee, Ji Won; Kim, Jin You
Background: The classic magnetic resonance imaging (MRI) feature of endometriomas is the shading sign, which is characterized by T2-shortening in ovarian cystic lesions that are hyperintense on T1-weighted images. The shading sign is infrequently observed in hemorrhagic ovarian cysts. Purpose: To investigate the value of MRI with diffusion-weighted imaging (DWI) for distinguishing endometriomas from hemorrhagic cysts in the ovary. Material and Methods: This retrospective study included 91 patients with 98 ovarian endometriomas and 21 hemorrhagic ovarian cysts that were confirmed pathologically, who had undergone MRI with DWI. Two radiologists compared MRI features, including size, bilaterality, multilocularity, the shading sign, the ovarian lesion/muscle signal intensity ratio at T2-weighted images, and T2 dark spots, between endometriomas and hemorrhagic cysts. We also compared the mean ADC value between endometriomas and hemorrhagic cysts, and determined the optimal cutoff ADC value for differentiating endometriomas from hemorrhagic cysts. Results: The size and mean ADC values were significantly different between endometriomas and hemorrhagic cysts. The mean ADC values of endometriomas and hemorrhagic cysts were 1.06 ± 0.38 × 10  −3  mm 2 /s and 0.73 ± 0.29 × 10 −3  mm 2 /s, respectively ( P  < 0.002). The optimal cutoff ADC value for differentiating endometriomas from hemorrhagic cysts was 0.849 × 10 −3  mm 2 /s (sensitivity, 77.6%; specificity, 76.2%). Conclusion: The addition of DWI could help in differentiating endometriomas from hemorrhagic cysts in the ovary, when conventional MRI is challenging.